1996
DOI: 10.1002/bjs.1800830207
|View full text |Cite
|
Sign up to set email alerts
|

Value of routine intraoperative cholangiography in detecting aberrant bile ducts and bile duct injuries during laparoscopic cholecystectomy

Abstract: A prospective study was performed to determine the frequency and type of bile duct abnormalities, and to determine whether routine use of intraoperative cholangiography during laparoscopic cholecystectomy might aid in the prevention of bile duct injuries. Overall, anatomical aberrations of the bile ducts were found in 98 (19 per cent) of 513 cholangiograms. The most common anomalies were at the hepatic confluence and constituted different types of right hepatic subsegmental ducts draining separately into the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
3
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 26 publications
2
72
3
3
Order By: Relevance
“…This is known as an accessory hepatic duct, an aberrant hepatic duct, a Luschka duct, or a subvesicle duct [3,12,14,21]. The incidence of accessory hepatic ducts is reported to range from 1.4% to 27% [12,14,[19][20][21], and the rate was 2.9% in our study for 1,044 patients examined before LC.…”
Section: Discussionmentioning
confidence: 59%
“…This is known as an accessory hepatic duct, an aberrant hepatic duct, a Luschka duct, or a subvesicle duct [3,12,14,21]. The incidence of accessory hepatic ducts is reported to range from 1.4% to 27% [12,14,[19][20][21], and the rate was 2.9% in our study for 1,044 patients examined before LC.…”
Section: Discussionmentioning
confidence: 59%
“…Several other studies have shown that a routine IOC can detect significantly more biliary injuries as well as unexpected biliary anatomy, which may have surgical relevance. Although it has not been shown to prevent all injuries, a routine IOC has enabled surgeons to limit and correct biliary injuries earlier, leading to significantly reduced costs and fewer overall operative procedures to correct injuries [22][23][24]. The false identification of the CBD as the cystic duct and aggressive efforts to stop bleeding are the most important causes for bile duct injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Safety of the IOC and reduction in both the incidence and severity of bile duct injuries have been well documented [18][19][20][21][22][23][24]. A Swedish study of over 50,000 cholecystectomies showed that the incidence of duct injuries was 29 % lower when IOC was used and the intention to use IOC reduced the risk of death post cholecystectomy by 62 % [25].…”
Section: Ioc-a Fundamental Requirement Of Lcbdementioning
confidence: 99%
“…One compelling reason to perform a cholangiography during laparoscopic cholecystectomy is its ability to help prevent common bile duct injuries [2,9,21]. However, even a brief review of the reports published by proponents of this strategy will show that common bile duct injury can occur even when cholangiography is performed routinely [1,2,4,15,17,18]. As far as silent stones are concerned, they are of questionable clinical importance.…”
Section: Discussionmentioning
confidence: 99%